On Learning Domains, Advanced Stimulation Technology, Experiential Learning, and Reflection in Nursing Education - Vico Chiang (Halla Newcastle Education and Research Center, 2014)
Bloom's Taxonomy of learning objectives and Kolb's theory of experiential learning theory (ELT) contribute widely to the practice of teaching and learning in various disciplines. Given the recent increasing popularity of using advanced simulation that aligns with the focus on ELT in nursing education, the author suggested that such teaching and learning approaches through realistically simulated practice with an emphasis on refection could contribute to the achievement of psycho-motor, cognitive, and affective domains of learning objectives. Based on this more integrated model, more studies may be conducted and contribute to the increasing body of literature regarding the outcomes of advanced simulation in nursing education.